Fracture parameter diagnostic method during staged multi-cluster fracturing based on distributed temperature sensing - Cao WEI; Haitao LI; Xiaohua ZHU; Nan ZHANG; Hongwen LUO; Kun TU; Shiqing CHENG (Petroleum Exploration and Development)
The Carter model is used to characterize the dynamic behaviors of fracture growth and fracturing fluid leakoff. A thermo-fluid coupling temperature response forward model is built considering the fluid flow and heat transfer in wellbore, fracture and reservoir. The influences of fracturing parameters and fracture parameters on the responses of distributed temperature sensing (DTS) are analyzed, and a diagnosis method of fracture parameters is presented based on the simulated annealing algorithm. A field case study is introduced to verify the model's reliability. Typical V-shaped characteristics can be observed from the DTS responses in the multi-cluster fracturing process, with locations corresponding to the hydraulic fractures. The V-shape depth is shallower for a higher injection rate and longer fracturing and shut-in time. Also, the V-shape is wider for a higher fracture-surface leakoff coefficient, longer fracturing time and smaller fracture width. Additionally, the cooling effect near the wellbore continues to spread into the reservoir during the shut-in period, causing the DTS temperature to decrease instead of rise. Real-time monitoring and interpretation of DTS temperature data can help understand the fracture propagation during fracturing operation, so that immediate measures can be taken to improve the fracturing performance.